Factors associated with inconsistent condom use among brothel-based Cambodian female sex workers - Vohith, Khol (2001)
This study used the secondary data from the Cambodian HIV/AIDS Behavioral Surveillance Survey (BSS) 1999. The design of the study was cross-sectional.The objectives of the study were to estimate the prevalence of inconsistent condom use and to determine factors associated with incosistent condom use of the brothel-based female sex workers (FSWs) in Cambodia.The study found that 34of the FSWs were inconsistent condom users (did not use condom all the time during the immediate past week). The multivariate analysis indicated that having sweetheart and having more than three regular customers were associated with inconsistent condom use. The FSWs who had sweetheart were 3.84 times more likely to use condom inconsistently than those who did not have (OR=3.84, CI:2.79-5.27, P value:0.000). Similarly, the FSWs who had more than three regular customers were 1.61 times more likely to be inconsistent in their condom use than those who did not have any (OR=1.16. 95%CI:1.06-2.43, P value:0.023).